Diagnosis and treatment of furcation-involved teeth - Nibali, Luigi, 1978- (Hoboken, NJ : Wiley, 2018)
'Diagnosis and Treatment of Furcation-Involved Teeth offers dental professionals a comprehensive review of the aetiology and diagnosis of furcation defects, including treatment options. Provides a practical manual for the successful diagnosis and treatment of a therapeutic challenge for general dentists and periodontists. Presents illustrative photographs of clinical cases and procedures. Offers a helpful chapter on patient-reported outcomes'--Provided by publisher.
8.4 Resective Procedures and Restorative Approaches8.5 Conclusions; References; Chapter 9: Furcation Tunnelling; 9.1 Introduction; 9.2 Indication; 9.3 Patient Selection; 9.4 The Tunnelling Procedure: Surgical Steps; 9.5 Postoperative Follow-Up and Oral Hygiene in the Furcation; 9.6 Types of Teeth; 9.7 Pulp Reaction; 9.8 Caries after Furcation Tunnelling; 9.9 Maintenance Phase; References; Chapter 10: Innovative and Adjunctive Furcation Therapy:; 10.1 Introduction; 10.2 Periodontal Endoscope; 10.3 Laser Therapy; 10.4 Photodynamic Therapy; 10.5 Air-polishing Devices; 10.6 Local Antimicrobials
Includes bibliographical references and index.
Print version record.
Keywords: Teeth -- Roots -- Furcation -- Treatment; Periodontal disease -- Treatment; Teeth -- Radiography; MEDICAL / Surgery / General; Periodontal disease -- Treatment; Teeth -- Radiography; Furcation Defects -- diagnosis; Furcation Defects -- therapy; Models, Animal; Electronic books